2005
DOI: 10.1002/ajmg.a.30995
|View full text |Cite
|
Sign up to set email alerts
|

Further delineation of the phenotype maps for partial trisomy 16q24 and Jacobsen syndrome by a subtle familial translocation t(11;16)(q24.2;q24.1)

Abstract: We report on two cases of distal monosomy 11q and partial trisomy 16q due to a familial subtle translocation detected by FISH subtelomere screening. Exact breakpoint analyses by FISH with panels of BAC probes demonstrated a 9.3-9.5 megabase partial monosomy of 11q24.2-qter and a 4.9-5.4 megabase partial trisomy of 16q24.1-qter. The index patient displayed craniofacial dysmorphisms, mild mental retardation and postnatal growth retardation, muscular hypotonia, mild periventricular leukodystrophy, patent ductus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
4
24
0
Order By: Relevance
“…In the literature, two other patients with partial 11q monosomy and partial 16q trisomy were reported [Sousa et al, 2004;Zahn et al, 2005]. In both cases, children shared clinical features with ours (Table I).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the literature, two other patients with partial 11q monosomy and partial 16q trisomy were reported [Sousa et al, 2004;Zahn et al, 2005]. In both cases, children shared clinical features with ours (Table I).…”
Section: Discussionsupporting
confidence: 68%
“…In our familial cases (Patients 1 and 2), as in the case described by Zahn et al [2005], the der(11)t(11;16) resulted from the malsegregation of a maternal balanced translocation. In the literature, maternal balanced translocations are frequently the source of 16q trisomies [Sousa et al, 2004], while only 8% of 11qter monosomies would be caused by a parental balanced translocation [Grossfeld et al, 2004].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…While the phenotypic expression of full trisomy 16 is well defined, reports on partial trisomies of distal 16q are rare [Paladini et al, ; Sousa et al, ; Zahn et al, ]. In particular, the phenotypic expression of the terminal 16q24 duplication is largely unknown since only seven cases have been reported to date [Brisset et al, ; Giardino et al, ; Zahn et al, ; Maher et al, ; Joly et al, ; Baker et al, ]. The attempt to define a genotype‐phenotype correlation in this trisomy is even more difficult because all previous cases were unbalanced translocations and the clinical manifestation was a result mainly of partial monosomy rather than trisomy.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] PT syndrome is a variant of Jacobsen syndrome in which 11q23.2-qter deletion causes mental and growth retardation, trigonocephaly, facial dysmorphism and malformations of heart, kidney, intestinal system and lower extremities. [15][16][17][18][19][20] The clinical phenotype of previously reported patients with PTJ syndrome varies with the location of the breakpoint. Although giant a-granules in the platelets and bone marrow dysmegakaryopoiesis in the proband suggested PT syndrome, haplotype analysis clearly showed that the entire region between 11q23.3 and 11q24.3 was intact in all of the family members.…”
Section: Discussionmentioning
confidence: 99%